Reducing food waste: how to make it work? A look at IWMI’s work on the international day of awareness of food loss and waste. - Perera, Tania (International Water Management Institute, 2023)
Despite nearly 800 million people going hungry in 2022, food loss and waste continue to undermine global food security and environmental goals, with up to 30% of food lost along supply chains or discarded after retail. On the International Day of Awareness of Food Loss and Waste, the International Water Management Institute (IWMI) spotlighted its two-decade commitment to turning food waste into value through composting and reuse initiatives, particularly in Sri Lanka. IWMI’s work promotes circular economy practices from composting and animal feed reuse to food redistribution while helping reduce landfill emissions and the burden on urban waste systems. Notably, informal partnerships between food services and peri-urban piggeries in Colombo exemplify how resource recovery can power local economies, though supply variability and regulatory gaps remain. In collaboration with the Food and Agriculture Organization, IWMI developed the National Roadmap on Urban Food Waste Prevention and Reduction, operational since 2021, which has inspired food banks and awareness programs. The institute also supports training and digital innovations, such as a mobile app linking food waste sources to users, reinforcing its role in shaping policy, practice, and public behavior toward achieving SDG 12.3.